IMPLEMENTASI PROBLEM BASED LEARNING BERBANTUAN YOUTUBE UNTUK MENINGKATKAN KREATIVITAS SISWA - Nasution, Puspa Riani; Rhamayanti, Yuni; Hutagalung, Roito (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to: first, to find out whether the implementation of Problem Based Learning assisted by YouTube can improve students' creativity in class VII 7 SMP Negeri 5 Padangsidimpuan. Second, to find out the increase in student activity towards mathematics learning through the Implementation of Problem Based Learning Assisted by YouTube in class VII - 7 SMP Negeri 5 Padangsidimpuan. Third, to find out the increase in teachers' ability in managing learning through the Implementation of Problem Based Learning Assisted by YouTube in class VII-7 SMP Negeri 5 Padangsidimpuan. This type of research is Classroom Action Research (CAR). Which consists of 2 cycles. The subjects of this study were class VII-7 consisting of 30 students. The results of the study showed that students' creativity abilities by implementing Problem Based Learning Assisted by YouTube in cycle 1 obtained with a minimum category of “Very poor”, which was 46.67% and in cycle II increased to 93.33% with a “Very Good” category. The increase from cycle 1 to cycle II was 46.66%. With the achievement indicator already achieved ? 80% Then for the results of observations of student activities in cycle 1 obtained 65.63% in the category